Accountability of Bali Regional Officers in Applying Good Governance Principles - I.G.A.AG Dewi Sucitawathi Pinatih; I Wayan Joniarta; Ni Luh Yulyana Dewi (Indonesian Association for Public Administration (IAPA), 2019)
Development in Bali is generally largely initiated, proposed, executed by the legislature, in this case the members of the Regional Representative Council, both the Provincial DPRD, Regency DPRD, Denpasar City DPRD. Conceptually, the legislature has the task of making policies, regulations and regional regulations (PERDA) in collaboration with executives. The fact is in Bali, it is precisely the people's representatives who sit in the DPRD dominating the planning process, and implementing policies such as submitting grants for both physical and non-physical development in the community. Submission of proposals for regional development is often bridged by legislative members, causing the existence and authority that the executive should have taken over by members of the legislature. Not infrequently this triggered the emergence of corrupt practices in the bureaucratic body. The purpose of this research is to find out how the accountability of Balinese officials in applying the principles of good governance. The research methods used were interview techniques, observation techniques, and documentation techniques. The results of this study were to obtain information about the accuracy of the implementation of the principles of good governance carried out by the legislature and executive in the Bali region.